Diversity of transgene integration and gene-editing events in wheat (Triticum aestivum L.) transgenic plants generated using Agrobacterium-mediated transformation - Lopos, Louie Cris; Bykova, Natalia V.; Robinson, Janeen; Brown, Susan; Ward, Kerry; Bilichak, Andriy (Frontiers in Genome Editing, 2023)
Improvement of agronomic traits in crops through gene editing (GE) relies on efficient transformation protocols for delivering the CRISPR/Cas9-coded transgenes. Recently, a few embryogenesis-related genes have been described, the co-delivery of which significantly increases the transformation efficiency with reduced genotype dependency. Here we characterized the transgenic and GE events in wheat (cv. Fielder) when transformed with the GROWTH-REGULATING FACTOR 4 (GRF4) and its cofactor GRF-INTERACTING FACTOR 1 (GIF1) chimeric gene. Transformation efficiency in our experiments ranged from 22% to 68%, and the editing events were faithfully propagated into the following generation. Both low and high copy number integration events were recovered in the T0 population with the various level of integrity of the left and right T-DNA borders. We also generated a population of wheat plants with ten different gRNAs targeting 30 loci in the genome. Comparison of the epigenetic profiles at the target sites and editing efficiency revealed a significant positive correlation between chromatin accessibility and mutagenesis rate. Overall, preliminary screening of the transgene quality and GE events in the T0 population of plants regenerated through the co-delivery of GRF-GIF can allow for the propagation of the best candidates for further phenotypic analysis.